2020
DOI: 10.21608/ejbo.2020.27849.1492
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Bicarbonate Supplements on Biodiesel Production and Valuable Biochemical Components of the Marine Eustigmatophyceae Nannochloropsis oculata (Droop)

Abstract: M ICROBIAL breeding media must be cost-effective, enable high growth, meet exact requirements and be readily available. The effect of different levels of sodium bicarbonate (SB) [25, 50, 75 and 100%] in the growth medium on the biochemical constituents (protein, carbohydrates, lipids, fatty acids, and amino acids) of the Nannochloropsis oculata was assessed compared to the F/2 Guillard standard medium. The obtained results revealed that the chemical constituents of N. oculata were influenced by the used level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…At the second phase algae were exposed only to the following LEDs sources (Alobeidi, China): Red 635 nm and Blue 465 nm for the cultivation duration completely without both of white light and green LED because it was also observed that photobiostimulation of green algae using green LEDs was not effective for lipid production because the green light was reflected, therefore the green microalgae were not absorbed the green light. Thus, photosynthetic organisms in energy absorption are dependent on the chemical nature of their constitutive pigments [18,19], thus red and blue LEDs were chosen as the wavelength for biomass production in the second phase culture. These wavelengths were selected based on previous studies [20][21][22][23].…”
Section: Photobiostimulation Using Ledsmentioning
confidence: 99%
“…At the second phase algae were exposed only to the following LEDs sources (Alobeidi, China): Red 635 nm and Blue 465 nm for the cultivation duration completely without both of white light and green LED because it was also observed that photobiostimulation of green algae using green LEDs was not effective for lipid production because the green light was reflected, therefore the green microalgae were not absorbed the green light. Thus, photosynthetic organisms in energy absorption are dependent on the chemical nature of their constitutive pigments [18,19], thus red and blue LEDs were chosen as the wavelength for biomass production in the second phase culture. These wavelengths were selected based on previous studies [20][21][22][23].…”
Section: Photobiostimulation Using Ledsmentioning
confidence: 99%